(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
Energy consumption in the general lighting system is the largest part of the society’s energy consumption, while the maintenance and operation of the system requires a large cost for each city. The article focuses on the types of street lighting and innovative innovative methods, and proposes an intelligent system-based consumption reduction solution for remote metering and light control technologies for LED lights. The results show that significant energy savings are achieved and the service life of the lights is extended.